Pengaruh Penerapan Green Accounting Terhadap Pertumbuhan Harga Saham dengan Profitabilitas sebagai Variabel Moderating pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016 – 2020 - A Wau, Servasius Endelson; Rina Asmeri; Yuli Ardiany (Ekasakti Pareso Jurnal Akuntansi, 2024)
For the period between 2016 and 2020, this analysis looks at how shareability plays a role as a green moderating factor in the relationship between green accounting and price increases for industrial businesses listed on the IDX (Indonesian Stock Exchange). Twenty-three Indonesia Stock Exchange- listed manufacturing businesses were chosen as the survey's sample. A total of 115 observations were picked using a systematic sampling strategy. The yearly data is obtained by using the IDX file. The research in this article is quantitative in nature. In this study, we used a documentation approach to collecting data. Statistics technique use moderate regression analysis (MRA). These findings demonstrated the beneficial impact of green accounting on stock prices. Profitability also reflects the link between rising share prices and green accounting